Tinjauan Yuridis Kerjasama Notaris Rekanan Bank Perspektif Kode Etik Notaris - Putra, Sukarno Juliansyah (Fakultas Syariah INSURI Ponorogo, 2023)
One of the ways notaries as public officials carry out promotions is by collaborating with bank partners. Collaboration with bank partners is a contractual contract, the existence of cooperation with bank partners places the partner notary as a priority in making authentic deeds involving the bank and the customer, and vice versa, the bank as one of the facing parties will be a priority for the notary in making the contents of the deed. This study aims to implement the principle of independence contained in the Notary's Code of Ethics regarding the notary cooperation agreement with bank partners and identify the impacts arising from the cooperation of notary bank partners.